Cardioplegic machine perfusion of hearts donated after circulatory death - Saemann, Lars; Wachter, Kristina; Großkopf, Anne; Pohl, Sabine; Georgevici, Adrian-Iustin; Hoorn, Fabio; Korkmaz-İçöz, Sevil; Karck, Matthias; Simm, Andreas; Szabó, Gábor (Journal of cardiovascular translational research, 2025)
We compared the effects of ex-vivo machine perfusion (EVMP) of hearts donated after circulatory death (DCD) with the single-shot solutions HTK-N and Del Nido cardioplegia (DNC) on left-ventricular (LV) contractility and myocardial microcirculation. In a DCD pig model, hearts were maintained by EVMP with hypothermic, oxygenated HTK-N (DCD-HTK-N; N = 8) or DNC (DCD-DNC; N = 8) followed by reperfusion with blood, including assessment of contractility and microcirculation with Laser-Doppler-Flow (LDF). We performed transcriptomics using microarrays. In DCD-HTK-N, the ESP, dp/dtmax and dp/dtmin were significantly higher (p < 0.05) compared to DCD-DNC. Relative LDF was higher in DCD-HTK-N vs. DCD-DNC. Pathways related to inflammatory mediators, cAMP, ion channels, intracellular signaling, and cell death were regulated differently. In DCD-HTK-N, longevity-associated pathways were up-, and ageing-associated pathways were downregulated. EVMP of DCD hearts with HTK-N results in a superior LV function, microcirculation, and regulation of pathways with short- and long-term relevance compared to DNC.
Gesehen am 16.01.2026